RESPONS FUNGSIONAL Menochilus sexmaculatus Fabricius dan Verania lineata Thunberg (Coleoptera: Coccinellidae) TERHADAP WERENG BATANG PADI COKLAT Nilaparvata lugens (Stål.) (Homoptera: Delphacidae) - , Friends Silaban, S.Si., Prof. Dr. Jesmandt Situmorang, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Functional response and feeding of the Menochilus sexmaculatus Fabricius and Verania lineata Thunberg againts brown planthopper Nilaparvata lugens (Stal.) were conducted at the Centre for Management of Biological Resources Laboratory Gadjah Mada University, Yogyakarta. Adults of M. sexmaculatus and V. lineata were collected from the rice field, of which the sex and the age were not known. All the predators were fasted for 24 hours before the study conducted. The two spesies of the predators were fed with Nilaparvata lugens. Each individual of M. sexmaculatus was fed with 3, 6, 9, 12, 15, 18, and 21individuals/24 hours, while individual of V. lineata was fed with 4, 8, 12, 16, 20, 24, and 28 individuals/24 hours. Treatment repeated five times. The number of individuals that were fed were counted in the next 24 hour after the predator released. The analysis of functional response follows the Holling method. The result showed that the functional response of M. sexmaculatus and V. lineata againts Nilaparvta lugens followed the Holling type II. The real maximum preying capability of an M. sexmaculatus adult was 7,24 individuals/24 hour and the result estimation according to the Holling was 23,78 individuals. Preying capability of M. sexmaculatus instar I, II, III, IV were 3,87 individuals/24 hour, 7,80 individuals/24 hour, 10,14 individuals/24 hour, 15,50 individuals/24 hour consecutively. The real maximum preying capability of V. lineata was 9 individual every day and the result using Holling method was 30,24 individuals.